A Review Of Food And Nutrition Communication And Promotion In Ghana - Parbey, P.; Aryeetey, R. (African Journal of Food, Agriculture, Nutrition and Development, 2022)
Dietary perception, behavior, and nutritional status can all be influenced by exposure to information. Behavior change communication that is appropriately designed and implemented is critical for motivating optimal dietary behavior. On the other hand, inadvertent or deliberate misinformation can drive unhealthy dietary behaviors. As part of the process to develop food-based dietary guidelines (FBDGs) for Ghana, this rapid evidence review examined the nature, extent, sources, and medium of food and nutrition information dissemination and promotion in Ghana. PubMed, Cochrane, Google Scholar, and Open Access Theses Dissertations (OATD) databases were searched systematically using keywords to identify relevant peer-reviewed and grey literature. The review included 31 documents, after excluding 1,302 documents for ineligibility (based on irrelevant titles, abstracts, and duplicates). Limited reporting of undernutrition was found in print and electronic media. Unhealthy foods, including sugar-sweetened beverages, snacks, yogurt, instant noodles, candy/chocolate, and ice cream were frequently advertised through various communication media. Children are highly exposed to food advertisements, which target them. Promotional characters, animation, billboards, front-of-store displays; product-branded books, and toys are common strategies for food marketing and advertisement in Ghana. The most frequently reported sources of health and nutrition information were television, radio, social media, health professionals, families, and friends. Children and adults experienced changes in food preferences and choices as a result of exposure to food advertising on television. The commonly used traditional media were radio and television; printed newspaper use has declined tremendously in the past decade. Social media use (particularly WhatsApp, Facebook, and YouTube) is highest in urban areas, and is growing rapidly; young adults are the most active users of social media platforms. Experts recommend regulation as a mitigation for nutrition miscommunication and inaccurate promotion. The current review highlights the need for regulation of food marketing, and advertisement to safeguard a healthy food environment in Ghana.
Research Article
Keywords: advertisement; promotion; diet; regulation; social media; food; Ghana